Calculation of the turbidity transport in Dinh An coastal zone - Vinh, Phan Ngoc; Ninh, Pham Van; Viet Lien, Nguyen Thi (Vietnam Journal of Mechanics, 1998)
In the paper, the results of the calculation of turbidity transport in Dinh An coastal area by using the software named RDPOL based on random walk techniques developed by CMERCS are presented. In previous study, the carried out numerical model has been verified well by remote sensing images for classification of the turbidity distribution of Red, Thai Binh, Han, Thu Bon, Sai Gon - Dong Nai and Mekong estuaries. In this study, computed results, that the complexity of the bathymetry, the river flow of the Mekong River system and seasonal monsoon winds are taken into account, are compared with the observed data at 19 stations including 10 stations in March and 9 stations in October, 1997 in Dinh An coastal zone and show its reasonable agreement. Some maps of turbidity distribution in the area have been carried out and several remarks have been made.